DYSFUNCTION AND DEMOGRAPHIC RISK IN THE IGHIU COMMON CASE STUDY: BUCERDEA VINOASĂ (PANGEEA, 2025)
Ighiu is the largest commune in Alba County and comprises the villages of Ighiu (the commune residence), Şard, Ighiel, Ţelna and Bucerdea Vinoasă. The population is very heterogeneous and has various occupations, both in agriculture and in other economic branches. The demographic aspects of the population in the commune and, in particular, of the population of Bucerdea Vinoasă village, are the subject of this paper. The structure of the population by age, fertility rate, economic aspects, migration and aging were studied, to find optimal solutions to prevent the reduction of population.
Keywords: demographic study; population evolution; structure; migration; aging